Levi's Denim Art Contest : Catalogue of Winners. (Mill Valley : Baron Wolman / Squarebooks, 1974)
Shire, Bill ; Ostrom, Steve ; Morris, Hopeton ; Aronson, Kay ; Inouye, Amy ; Crandell Kerr, Louise ; Musashi, Sandra ; Comment, Constance ; Havis, C. Kenneth ; Kartes, Cheryl ; Rostock, Maddy ; Mercer, Mara ; etc.
Engels
boek